Pengaruh Komitmen Organisasi, Gaya Kepemimpinan, dan Lingkungan Kerja terhadap Intensitas Bertahan Karyawan Kantor PT. Perkebunan Musirawas Citraharpindo (Kalimantan Tengah) - Meysa Dwi Krismonika; Christantius Dwiatmadja (International Journal of Social Science and Business, 2020)
This research aim to determine the effect of the organization commitment, leadership style and work environment toward the intensity of the employees to stay on PT. Perkebunan Musirawas Citraharpindo office partially and simultaneously. This research is a casual research. The data collection method was using questionaires in the form of a questionaire distributed to 106 respondents. The data analysis method was using multiple linear regression analysis with IBM SPSS Statistics version 24. Result of the research shows that (1) there is no partial effect between organizional commitment and the intention to stay, (2)  Leadership style has no partial effect toward the intention to stay, (3) Work environment has no effect toward the intention to stay,(4) while the simultaneous way has an effect equal to 1.6% between the organization commitment, leadership style, and work environment variable toward the intention of the employees to stay on PT. Perkebunan Musirawas Citraharpindo office.